Clinical, Hormonal, and Neuroradiological Characteristics and Therapeutic Outcomes of Prolactinomas in Children and Adolescents at a Single Center - Yang, Aram; Cho, Sung Yoon; Park, Hyojung; Kim, Min Sun; Kong, Doo-Sik; Shin, Hyung-Jin; Jin, Dong-Kyu (Frontiers in Endocrinology, 2020)
Background/purpose: A prolactinoma is the most common pituitary adenoma, but it is relatively rare in childhood and adolescence. There is only limited research about the clinical spectrum, treatment, and outcomes of prolactinomas in childhood and adolescence. In this single-center cohort study, we assessed the clinical, hormonal, and neuroradiological characteristics and therapeutic outcomes of children and adolescents with prolactinomas. Methods: This retrospective cohort study included 25 patients with prolactinomas diagnosed before 19 years of age, who presented at Samsung Medical Center during a 15-year period (March 2005 to August 2019). Results: The median age at diagnosis was 16.9 (range 10.1–18.5) years, and 80% of the patients were female. The common clinical manifestations at diagnosis were galactorrhea (10/20, 50%) and amenorrhea (9/20, 45%) among females and visual field defects (3/5, 60%) and headaches (2/5, 40%) among males. In our cohort, macroadenomas accounted for 56% of cases, and the rate of overall responsiveness to dopamine agonists (DAs) was 56% (10/18). Male gender, the prolactin (PRL) level at diagnosis, and the presence of panhypopituitarism were positively correlated with maximum tumor diameter (r = 0.443, P = 0.026; r = 0.710, P < 0.001; and r = 0.623, P = 0.001, respectively). After the trans-sphenoidal approach (TSA), 53% (8/15) of patients showed normalization of the PRL level. Three patients, who underwent gamma knife surgery (GKS) owing to either resistance or intolerance to DAs or recurrence after the TSA, achieved a normal PRL level accompanied with marked tumor reduction and symptom remission. Conclusions: A macroprolactinoma is more prevalent than a microprolactinoma in children and adolescents than in adults. Male gender, increased PRL levels, and the presence of panhypopituitarism at diagnosis are closely related to macroprolactinomas in children and adolescents.